Pengaruh Pembelajaran Mata Kuliah Character Building (CB) Self Development Terhadap Perilaku Mahasiswa Sastra China Angkatan 2010 Universitas Bina Nusantara Jakarta - Hari Sriyanto (Bina Nusantara University, 2020)
Learning Character Building / Character Building (CB): Self Development is a compulsory subject taught to students of Bina Nusantara University in semester 1 or semester 2. This study aims to determine and examine the effect of ability to know yourself, ability to accept yourself , and attitudes simultaneously and partially towards the behavior of Chinese Literature Force students in 2010 at Bina Nusantara University after attending and receiving the Character Building (CB) course I: Self Development. The sample in this study amounted to 70 students of Chinese Literature in 2010. This research is an explanatory research (Explatanatory Research) and also correlational research to see the relationship between variables. The data in this study are primary data obtained from questionnaires given to respondents directly. The results obtained indicate that the ability to know oneself, the ability to accept oneself, and attitudes have a significant and simultaneous influence on the behavior of Chinese Literature students at Bina Nusantara University in 2010.